2022
DOI: 10.1088/2515-7620/acabb6
|View full text |Cite
|
Sign up to set email alerts
|

The nexus of carbon dioxide emissions, economic growth, and urbanization in Saudi Arabia

Abstract: Saudi Arabia has implemented its ambitious and comprehensive national strategy, i.e., Saudi Vision 2030, to achieve major economic, social, and environmental objectives. The main aim of this paper is to study the Granger causality relationships between economic growth, environmental degradation, and urbanization in Saudi Arabia over the period from 1985 to 2019. At first, Augmented Dicky-Fuller (ADF) and Phillips-Perron (PP) tests were applied in order to check the stationarity of the panel time-series data. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…In the paper, the authors also provided a comprehensive summary of existing empirical studies in this area. A similar study and analysis was conducted by Alajlan and Alreshaidi (2022). Abid et.…”
Section: Literature Reviewmentioning
confidence: 86%
“…In the paper, the authors also provided a comprehensive summary of existing empirical studies in this area. A similar study and analysis was conducted by Alajlan and Alreshaidi (2022). Abid et.…”
Section: Literature Reviewmentioning
confidence: 86%
“…For example, research in 17 Asia-Pacific countries from 1960 to 2020 showed that economic growth harmed the environment, increasing CO2 emissions (Rahman & Alam, 2022). Then, research took place in Saudi Arabia from 1985 to 2019, resulting in economic growth that contributed to increasing CO2 emissions (Alajlan & Alreshaidi, 2022). This is because economic growth in the four countries during the period of 2015-2020 experienced an increase in energy consumption: as the economy grows, energy consumption tends to rise.…”
Section: Discussionmentioning
confidence: 99%
“…These studies examined behaviors from the perspective of environmental significant behavior (Stern 2000), public participation (Zhang et al 2022), environmental responsibility (Magnier and Schoormans 2015), and pro-environment action (Su et al 2018) for constructing ecological civilization and realizing sustainable development. (Kuznet 1995) raised an environment Kuznets curve (EKC) model which has produced extensive influences in worldwide researches of environmental management (Panayotou 1993, Usama et al 2015, Naif and Amirah 2022. However, many researchers have found that the EKC model was not universal and there would be other factors besides economic growth that influence on environment pollution (Pearson 1994, De Bruyn et al 1998, Wagner 2015, Sanchez and Stern 2016.…”
Section: Introductionmentioning
confidence: 99%